A study of genomic diversity in populations of Maharashtra, India, inferred from 20 autosomal STR markers - Ashish Badiye; Neeti Kapoor; R. K. Kumawat; Shivani Dixit; Aditi Mishra; Akansha Dixit; Prachi Kathane; Sudeshna Bag; Vaishnavi Thakre; Kamlesh Kaitholia; Ankit Srivastava; Gyaneshwer Chaubey; et al. (BMC Research Notes, 2021)
Abstract Objective This study was planned to evaluate the genetic diversity in the admixed and Teli (a Hindu caste) populations of Maharashtra, India using 20 autosomal Short Tandem Repeat (STR) genetic markers. We further investigated the genetic relatedness of the studied populations with other Indian populations. Results The studied populations showed a wide range of observed heterozygosity viz. 0.690 to 0.918 for the admixed population and 0.696 to 0.942 for the Teli population. This might be due to the multi-directional gene flow. The admixed and Teli populations also showed a high degree polymorphism which ranged from 0.652 to 0.903 and 0.644 to 0.902, respectively. Their combined value of matching probability for all the studied loci was 4.29 × 10–25 and 5.01 × 10–24, respectively. The results of Neighbor-Joining tree and Principal Component Analysis showed that the studied populations clustered with the general populations of Jharkhand, UttarPradesh, Rajasthan and Central Indian States, as well as with the specific populations of Maharashtra (Konkanastha Brahmins) and Tamil Nadu (Kurmans). Overall, the obtained data showed a high degree of forensic efficacy and would be useful for forensic applications as well as genealogical studies.